Fires and volcanic activity: History of fire in the Mexico basin during late Pleistocene based on carbonized material records in the Chalco lake - Rodrigo Martínez-Abarca; Socorro Lozano-García; Beatriz Ortega-Guerrero; Margarita Caballero-Miranda (Revista Mexicana de Ciencias Geológicas)
Forest fires, considered as free and not programmed fire propagation, are perturbations that greatly alter ecosystems. During fires, variable quantities of charcoal particles are produced by the burning vegetation, which can be later deposited in lacustrine basins. The traditional charcoal size particle model associates the > 100 µm primary particles to local fire events, within the watershed, and the < 100 µm particles are linked to regional fire events, outside the watershed. Fires can be related with favorable climatic conditions, but in tectonically active areas like the basin of Mexico, volcanism can also be a factor producing fires and charcoal particles. We document the history, intensity and frequency of fires recorded in the lacustrine sediments of lake Chalco (core CHAVII-11), by performing a high-resolution charcoal particle analysis in sediments deposited before and after three main volcanic events.  The sources of these events had different distances to lake Chalco: Tláhuac tephra (TTH; 28690 years cal BP), probably produced by the Teuhtli volcano, was a local event; the Tutti Frutti Pumice (PTF; 17000 years cal BP) produced by the Popocatépetl volcano, was an extra-local event and the Upper Toluca Pumice (PTS; 12300 years cal BP) produced by the Nevado de Toluca volcano, was a regional event.  Charcoal accumulation rates (CHAR) and distribution of size particles indicate that paleoclimate was a direct factor defining the intensity and recurrence of fires before and after volcanic activity, as climate defines vegetation type and density, and therefore fuel availability.  Fires before and after the TTH were frequent, local and intense in comparison with fires reconstructed before or after the PTF and PTS events. CHAR values were lower during the more widespread PTF event, than for the local TTH event, although the highest CHAR values were recorded for the most distant, regional, and intense PTS event. These results show that charcoal accumulation rates during the volcanic events in central Mexico cannot be interpreted following traditional model of charcoal particle dispersion. This model have important restrictions in active volcanic regions such as central Mexico.